Cryogenic Ion Spectroscopy of a Singly Protonated Peptide DYYVVR: Locating Phosphorylation Sites of a Kinase Domain - Kwon, Jang Han; Lee, Min Ji; Song, Gyeongok; Tsuruta, Kazuya; Ishiuchi, Shun Ichi; Fujii, Masaaki; Kang, Hyuk (Journal of Physical Chemistry Letters, 2020)
Cryogenic ion spectroscopy (CIS) was applied to singly protonated DYYVVR, a tryptic peptide that contains the two active tyrosine residues (Y980 and Y981) of the Janus kinase 3 (JAK3) kinase domain, together with its point mutants (Y980F and Y981F) and phosphorylated peptides (pY980, pY981, and pY980pY981). The two tyrosine chromophores showed distinguishable UV absorption bands at around 35 200 and 35 450 cm-1, respectively. By comparing with the point mutants, the lower electronic band was assigned to the absorption of Y981, and the higher one was assigned to Y980. When phosphorylated, the UV absorption of the phosphorylated chromophore shifts to higher energy above 36 500 cm-1 but the unphosphorylated chromophore gives the absorption in the same region. Conformer-specific IR spectroscopy and density functional theory (DFT) calculations were used to tentatively assign the structure of DYYVVR. Two conformations were found, where Y981 is solvated by the protonated side chain of arginine R984, and the orientation of the carboxylic OH of D979 was different between the two. It is demonstrated that CIS can be used to distinguish the two tyrosine chromophores and to locate the phosphorylation site of a kinase domain.
Keywords: Electronic band; Ion spectroscopies; Kinase domains; Phosphorylated peptides; Phosphorylation sites; Protonated peptides; Tryptic peptides; Tyrosine residues; Amino Acid Sequence; Binding Sites; Models, Molecular; Oligopeptides; Phosphorylation; Protein Domains; Protein Kinases; Protons; Spectrum Analysis